Examining the Occupational Safety and Health Hazards encountered by Municipal Waste Collectors in Murewa Rural District Council, Zimbabwe - Intauno, Kudakwashe; Poshai, Leon (International Journal of Law and Public Policy (IJLAPP), 2023)
The failure of Zimbabwean local authorities to implement contemporary waste management technology, combined with refuse management incapacity exposes handlers of solid waste to work-related diseases and accidents. The study sought to use Murewa Rural District Council (RDC) as a case study and a mixed-method that triangulated qualitative and quantitative research methodologies was employed as a method of inquiry. The study established that, in Murewa, there is an irregular garbage collection schedule which results in piles of uncollected refuse on roadsides, street corners and other undesignated areas. The illegal dumping of refuse and overflowing of garbage bins have become an eyesore in Murewa Township Centre. The people employed to clean this mess are often ill equipped to clean the garbage in hygienic ways as they often use their bare hands to shovel the garbage from dumpsites and overloaded bins into the refuse collection trucks. In doing this, these workers are exposed to biological hazards such as bacteria, fungi, viruses, parasites and cysts. To minimise the associated hazards, the study suggests, among other things, that the Murewa Rural District Council should improve workplace safety and health for employees by modifying workplace and process design and by adhering to the hazard identification and risk assessment methodology.